2008
DOI: 10.1038/ajh.2008.343
|View full text |Cite
|
Sign up to set email alerts
|

Renin–Angiotensin System and α-Adducin Gene Polymorphisms and Their Relation to Responses to Antihypertensive Drugs: Results From the GENRES Study

Abstract: Common polymorphisms of ADD1, AGT, ACE, and AGTR1 do not markedly predict BP responses to amlodipine, bisoprolol, HCT, and losartan, at least in white hypertensive men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Although the studies varied greatly in population ancestry and selection criteria, duration, and response phenotypes, generally the fi ndings were consistent with hypotheses: individuals with "poor metabolizer" genotypes had higher plasma drug concentrations and greater BP reduction than those with "intermediate" to "ultra rapid metabolizer" genotypes [46][47][48][49][50]. Neither Gerhard et al [51] nor Suonsyrja et al [22] reported signifi cant associations with ADD1 (Gly460Trp), the former with atenolol in a study of long-term clinical end points and the latter with bisoprolol in a 4-week study of BP response. Suonsyrja et al's [22] study also found no signifi cant associations with AGT (Met235Thr), ACE (ID), or AGTR1 (1166A/C).…”
Section: (Continued)supporting
confidence: 72%
See 3 more Smart Citations
“…Although the studies varied greatly in population ancestry and selection criteria, duration, and response phenotypes, generally the fi ndings were consistent with hypotheses: individuals with "poor metabolizer" genotypes had higher plasma drug concentrations and greater BP reduction than those with "intermediate" to "ultra rapid metabolizer" genotypes [46][47][48][49][50]. Neither Gerhard et al [51] nor Suonsyrja et al [22] reported signifi cant associations with ADD1 (Gly460Trp), the former with atenolol in a study of long-term clinical end points and the latter with bisoprolol in a 4-week study of BP response. Suonsyrja et al's [22] study also found no signifi cant associations with AGT (Met235Thr), ACE (ID), or AGTR1 (1166A/C).…”
Section: (Continued)supporting
confidence: 72%
“…A2RB-angiotensin II receptor blocker; ACEI-angiotensin-converting enzyme inhibitor; BB-β-blocker; BP-blood pressure; CAD-coronary artery disease; CCB-calcium channel blocker; CHD-coronary heart disease; CVD-cardiovascular disease; ESRD-end-stage renal disease; HCTZ-hydrochlorothiazide diuretic; HF-heart failure; HTN-hypertension; LV-left ventricular; MI-myocardial infarction; PGx-pharmacogenetic; US-United States. [38] (see also [31,39] [22] (see also [24][25][26] (see also [25] † ) *Associations reported here met standards of signifi cance as defi ned by each study. † Selected references provided for context.…”
Section: Adrenergic Receptor Antagonistsmentioning
confidence: 91%
See 2 more Smart Citations
“…The ADD1 variant rs4961 has been studied extensively on its own. However, results have been conflicting as the T allele has been found to confer increased diuretic efficacy in some studies, but reduced efficacy in others 42,[75][76][77][78][79][80][81][82][83][84] .…”
Section: Candidate Variants Contributing To Sodium Reabsorptionmentioning
confidence: 99%